Viet Nam Alive & Thrive Process Evaluation Survey 2013: Commune General Information - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the community survey conducted to gather data for process evaluation in the context of an overall evaluation of the franchise model for Alive & Thrive (A&T) in Viet Nam. The overall aims of the evaluation were to assess the impact of the franchise model on (1) age-appropriate IYCF practices among children <2 years of age and (2) stunting among children 2-5 years of age. A&T is an initiative funded by the Bill & Melinda Gates Foundation to reduce undernutrition and death caused by suboptimal IYCF practices in three countries (Viet Nam, Bangladesh, and Ethiopia) over a period of six years (2009-2014). The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing the stunting of children under two years of age. A&T applied principles of social franchising within the government health system to deliver the interventions. A&T’s Viet Nam strategy is designed to support improvements in infant and young child feeding (IYCF) in three key ways: (1) improving policy and regulatory environments; (2) shaping IYCF demand and practice; and (3) increasing supply, demand, and use of fortified complementary foods. In order to achieve this, the A&T Viet Nam program has been divided into three main focus areas namely advocacy, community, and the private sector. In addition, a communications component is integrated into each of these focus areas to support their activities. Among several activities, the franchise model is a core initiative of the community model to provide quality nutrition counseling to women and families at health facilities at all levels. Implemented in cooperation with the Vietnamese government and select private clinics, franchises will deliver a package of focused IYCF counseling services to pregnant women, lactating mothers, and their families, based on a franchise service package. Focused training and capacity building for healthcare workers will be undertaken to enable the health system to provide franchise services. Individualized services will be supported through mass media campaigns aimed at generating demand for franchise services and promoting optimal IYCF practices. The process evaluation survey was conducted in 40 communes across four provinces, Thai Nguyen, Thanh Hoa, Quang Ngai, and Vinh Long, between June and August 2013 by the IFPRI team in collaboration with the Institute of Social and Medicine Studies (ISMS). The survey included two major components—(i) household survey, and (ii) frontline health workers survey. The survey of frontline health workers (FHWs) included questionnaires for commune health centers (CHC) staff, village health workers (VHWs) involved in the A&T interventions, as well as a commune questionnaire. The commune general information data are generated using commune questionnaire and provide information about the community such as number of villages in each commune, population, number of health facilities, number of personnel in the health facility, number of children under 5 years of age, and availability of information, communication, and education (IEC) items materials.